Pronto: A Multi-Sensor State Estimator for Legged Robots in Real-World Scenarios - Camurri, Marco; Ramezani, Milad; Nobili, Simona; Fallon, Maurice (Frontiers in Robotics and AI, 2020)
In this paper we present a modular and flexible state estimation framework for legged robots operating in real world scenarios, where environmental conditions such as occlusions, low light, rough terrain and dynamic obstacles can severely impair estimation performance. At the core of the proposed estimation system, called Pronto, is an Extended Kalman Filter (EKF) which fuses IMU and Leg Odometry sensing for pose and velocity estimation. We also show how Pronto can integrate pose corrections from visual and LIDAR and odometry to correct pose drift in a loosely coupled manner. This allows it to have a real- time proprioceptive estimation thread running at high frequency (250–1000 Hz) for use in the control loop while taking advantage of occasional (and often delayed) low frequency (1–15 Hz) updates from exteroceptive sources, such as cameras and LIDARs. To demonstrate the robustness and versatility of the approach, we have tested it on a variety of legged platforms, including two humanoid robots (the Boston Dynamics Atlas and NASA Valkyrie) and two dynamic quadruped robots (IIT HyQ and ANYbotics ANYmal) for more than 2 h of total runtime and 1.37 km of distance traveled. The tests were conducted in a number of different field scenarios which the conditions described above. The algorithms presented in this paper are made available to the research community as open-source ROS packages.